2012
DOI: 10.1002/ca.22094
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging investigation of the atlanto‐axial interspace

Abstract: The objective of this study is to examine the anatomy of the atlanto-axial interspace using magnetic resonance (MR) imaging. Two hundred and forty MR images of living subjects were examined for the presence of a posterior dural prominence and oblique hypointense fibers between the first and second cervical neural arches. Of the 240 images analyzed, 64% revealed a posterior concavity of the cervical dura mater. Of this, 24% also revealed oblique, linear hypointense fibers that appeared to be in direct contact w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…In the past 20 years, the findings confirm that the RCPmi is connected to the cervical spinal dura mater via the MDB through the posterior antlanto-occipital interspace (Hack et al;Scali et al, 2013;Pontell et al;Su et al;Zheng et al). It is hypothesized to perform some physiological functions, such as protecting the spinal cord from dural enfolding (Hack et al;Pontell et al;Chang et al;Fernández-de-Las-Peñas et al, 2008;McPartland et al), placing tension to the dura under (Rutten et al, 1997;Chang et al;Fernández-de-Las-Peñas et al, 2008;McPartland et al), maintaining the integrity of the subarachnoid space (Fernández-de-Las-Peñas et al, 2008;McPartland et al), and working as a pump via the MDBs to provide power for CSF circulation (Su et al; Zheng et al; Yuan et al).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In the past 20 years, the findings confirm that the RCPmi is connected to the cervical spinal dura mater via the MDB through the posterior antlanto-occipital interspace (Hack et al;Scali et al, 2013;Pontell et al;Su et al;Zheng et al). It is hypothesized to perform some physiological functions, such as protecting the spinal cord from dural enfolding (Hack et al;Pontell et al;Chang et al;Fernández-de-Las-Peñas et al, 2008;McPartland et al), placing tension to the dura under (Rutten et al, 1997;Chang et al;Fernández-de-Las-Peñas et al, 2008;McPartland et al), maintaining the integrity of the subarachnoid space (Fernández-de-Las-Peñas et al, 2008;McPartland et al), and working as a pump via the MDBs to provide power for CSF circulation (Su et al; Zheng et al; Yuan et al).…”
Section: Discussionmentioning
confidence: 65%
“…The suboccipital region is a complex anatomical structure with the rectus captis posterior major (RCPma), the rectus capitis posterior minor (RCPmi), and the obliquus capitis inferior (OCI) as part of an important anatomical structure in this region for connecting with the dura mater via the myodural bridge (MDB) (Hack et al, 1995;Pontell et al, 2013;Scali et al, 2013;Su et al, 2013;Zheng et al, 2014). In the past 20 years, it was proposed that through the MDBs the RCPmi might perform some physiological functions, like protecting the spinal cord from dural enfolding (Chang et al, 1992;Hack et al;McPartland et al, 1997;Fernández-de-Las-Peñas et al, 2008;Pontell et al), placing tension to the dura under (Chang et al;McPartland et al;Rutten et al, 1997;Fernández-de-Las-Peñas et al, 2008;), maintaining the integrity of the subarachnoid space (McPartland et al;Fernández-de-Las-Peñas et al, 2008), and working as a pump via the MDBs to provide power for CSF circulation (Su et al;Zheng et al;Yuan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…On integrating the findings of these literatures with our results, it seems reasonable to suggest that the Suboccipital Myodural Bridge through the atlantoaxial interspace is part of the VDL and that the related suboccipital muscles may directly exert a force on the cervical dura mater via the VDL. Moreover, Scali et al [8] reported the presence of a posterior dural bulge at C1–C2 in a significant sample size of the MR image population, for which the physiological contraction of the suboccipital muscles and the movements of the head and neck may be a reasonable explanation. These possible correlations require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed multiple soft-tissue connections extending from the suboccipital structures to the cervical dura mater through the posterior intervertebral spaces [1][5]. Thus, these connections can be regarded as fibrous fascial tissue bridges providing a continuity of the suboccipital muscles, integrating motion of the atlantooccipital and cervical intervertebral joints with that of the cervical dura mater [2], [5][8]. All of these reports clearly show that the suboccipital region is one of the most complex anatomical regions in the human body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation